Registered Reports: Genre Evolution and the Research Article. (January 2019) - Mehlenbacher, Ashley Rose
The research article is a staple genre in the economy of scientific research, and although research articles have received considerable treatment in genre scholarship, little attention has been given to the important development of Registered Reports. Registered Reports are an emerging, hybrid genre that proceeds through a two-stage model of peer review. This article charts the emergence of Registered Reports and explores how this new form intervenes in the evolution of the research article genre by replacing the central topoi of novelty with methodological rigor. Specifically, I investigate this discursive and publishing phenomenon by describing current conversations about challenges in replicating research studies, the rhetorical exigence those conversations create, and how Registered Reports respond to this exigence. Then, to better understand this emerging form, I present an empirical study of the genre itself by closely examining four articles published under the Registered Report model from the journal Royal Society Open Science and then investigating the genre hybridity by examining 32 protocols (Stage 1 Registered Reports) and 77 completed (Stage 2 Registered Reports) from a range of journals in the life and psychological sciences. Findings from this study suggest Registered Reports mark a notable intervention in the research article genre for life and psychological sciences, centering the reporting of science in serious methodological debates.